2020
DOI: 10.1016/j.celrep.2020.108181
|View full text |Cite
|
Sign up to set email alerts
|

Scavenging of Labile Heme by Hemopexin Is a Key Checkpoint in Cancer Growth and Metastases

Abstract: SUMMARY Hemopexin (Hx) is a scavenger of labile heme. Herein, we present data defining the role of tumor stroma-expressed Hx in suppressing cancer progression. Labile heme and Hx levels are inversely correlated in the plasma of patients with prostate cancer (PCa). Further, low expression of Hx in PCa biopsies characterizes poorly differentiated tumors and correlates with earlier time to relapse. Significantly, heme promotes tumor growth and metastases in an orthotopic murine model of PCa, with the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 95 publications
5
45
0
Order By: Relevance
“…This expression is significantly reduced in Hmox1 −/− HSCs, which may result in the decreased uptake of heme. Recently, Canesin et al described heme-overload-induced changes in expressions of cell-cycle regulating genes [ 11 ]. We checked that these changes are not reflected by the gene expression profile in Hmox1 −/− HSCs ([ 42 ], data not shown), suggesting that Hmox1 −/− HSCs do not have significantly elevated free heme.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This expression is significantly reduced in Hmox1 −/− HSCs, which may result in the decreased uptake of heme. Recently, Canesin et al described heme-overload-induced changes in expressions of cell-cycle regulating genes [ 11 ]. We checked that these changes are not reflected by the gene expression profile in Hmox1 −/− HSCs ([ 42 ], data not shown), suggesting that Hmox1 −/− HSCs do not have significantly elevated free heme.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they could provide an additional element in the regulation of various biological functions. Very recently, the importance of G-quadruplexes in the promoter sequence for regulating the expression of c-Myc in prostate cancer cells has been directly demonstrated [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, ferritin (FT) decrease can result from activation of MYC, IRP2, or p53 mutation [51,155,185]. Such a vicious cycle is sustained as increased LIP promotes CDK, JAK/STAT, PI3K, MAPK/ERK pathways [172], whereas heme can further enhance ERK and MYC and inhibits p53 [181,186,187]. Lipocalin 2 (LCN2 or NGAL) is a soluble iron-binding glycoprotein expressed mainly by neutrophils [188].…”
Section: Cellular Iron Dysregulation In Cancermentioning
confidence: 99%
“…In leukemia and lung cancer cells, increased heme synthesis and availability also increased cell proliferation by enhancing mitochondrial oxidative metabolism [214][215][216]. Furthermore, recent studies have demonstrated that labile heme fosters cell proliferation by inhibiting p53 [187] and inducing MYC [186]. Interestingly, heme was shown to interfere directly with the p53 gene in vitro and in vivo while inducing proteosomal degradation of p53 protein [187].…”
Section: Cellular Iron Dysregulation In Cancermentioning
confidence: 99%